1975
DOI: 10.1212/wnl.25.11.1071
|View full text |Cite
|
Sign up to set email alerts
|

The saccade velocity test

Abstract: Scatter plots showing the amplitude versus velocity (maximum and average) relationship of horizontal saccades in 25 normal subjects and four groups of patients were statistically compared. Three patients with "subclinical" medial longitudinal fasciculus syndromes had significant slowing of adducting saccades, and two of these patients had unsuspected slowing of abducting saccades (although to a lesser degree). Five patients with olivopontocerebellar degeneration and three patients with myotonic dystrophy had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
1

Year Published

1976
1976
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(62 citation statements)
references
References 11 publications
6
55
1
Order By: Relevance
“…Saccadic eye movements, however, can be recorded continuously to follow drug effects developing over the course of a few minutes and will therefore have an important future application in pharmacokinetic and pharmacodynamic studies of benzodiazepine drugs and perhaps of other compounds, which are shown to affect these movements. Furthermore peak saccadic velocity and saccade duration can be easily quantified and they are beyond voluntary control once initiated (Baloh et al, 1975).…”
Section: Eye Movement Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saccadic eye movements, however, can be recorded continuously to follow drug effects developing over the course of a few minutes and will therefore have an important future application in pharmacokinetic and pharmacodynamic studies of benzodiazepine drugs and perhaps of other compounds, which are shown to affect these movements. Furthermore peak saccadic velocity and saccade duration can be easily quantified and they are beyond voluntary control once initiated (Baloh et al, 1975).…”
Section: Eye Movement Testsmentioning
confidence: 99%
“…There is now substantial evidence that peak saccadic velocity and saccade duration at 300 of amplitude are indicators of the function of a well defined group of neurones in the brain stem reticular formation (Keller, 1974). Saccade reaction time is considered to be an indicator of the sensory input to the saccadic system (Baloh et al, 1975), and offers a convenient means of assessing the function of higher parts of the central nervous system, such as the 0306-5251/83/0100-0103 $02.00 cortical lobes and the superior colliculus, encoding visual information (Solingen et al, 1977, Rothenberg, etal., 1980. The eye movement technique has successfully been used to measure central effects of alcohol (Baloh et al, 1979;Lehtinen et al, 1979;Bittencourt et al, 1980;Tedeschi et al, 1982a), benzodiazepines (Bittencourt et al, 1981, Rothenberg & Selkoe, 1981 methadone (Rotheberg etal., 1980), amylobarbitone (Tedeschi et al, 1982b) and amphetamine (Tedeschi etal., 1982c …”
Section: Introductionmentioning
confidence: 99%
“…They are defined by a set of characteristic relationships between amplitude, duration, and peak velocity. These stereotyped relationships (sometimes referred to as the "main sequence") have been described in detail during horizontal, vertical, and oblique movements in a variety of species (Bahill et al 1975;Baloh et al 1975;Becker and Jürgens 1990;Collewijn et al 1988a,b;Evinger et al 1981;Fuchs 1967;Guitton and Mandl 1980;King et al 1986;Smit et al 1990;van Gisbergen et al 1985;Yee et al 1985). For example, the positive correlation between saccade duration and amplitude during horizontal saccades is illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Peak saccade velocity and saccade duration are indicators of brain stem reticular formation function (Keller, 1974) (Becker & Fuchs, 1970;Baloh et al, 1975a).…”
Section: Physiology Of Saccadic Eye Movementsmentioning
confidence: 99%